Test of the Cosmic Transparency with the Baryon Acoustic Oscillation and Type Ia Supernova Data*Supported by the National Natural Science Foundation of China under Grant Nos 11175093, 11222545, 11435006 and 11375092, and the K. C. Wong Magna Fund of Ningbo University. (May 2016) - Li 李, He-Kun 合昆; Wu 吴, Pu-Xun 普训; Yu 余, Hong-Wei 洪伟
Abstract : We use the latest baryon acoustic oscillation and Union 2.1 type Ia supernova data to test the cosmic opacity between different redshift regions without assuming any cosmological models. It is found that the universe may be opaque between the redshift regions 0.35–0.44, 0.44–0.57 and 0.6–0.73 since the best fit values of cosmic opacity in these regions are positive, while a transparent universe is favored in the redshift region 0.57–0.63. However, in general, a transparent universe is still consistent with observations at the 1σ confidence level.